Semi-artificial seed production technique of Anabas testudineus (kawai) in pond - Sarma, Kamal; Singh, Jaspreet; Ahirwal, S K; Kumar, Tarkeshwar (Indian Farming, 2023)
Anabas testudineus, also known as the climbing perch, is an important air-breathing freshwater species distributed throughout India and other South-Asian countries. It fetches good market value, especially in West Bengal, Assam, Tripura and Bihar, because it contains easily digestible fat, essential amino acids and minerals. It is considered to be one of the most potential species for aquaculture in India. Recently, its population has drastically reduced from the natural water bodies and become a threatened species. However, culture practices of this species are not much popularised in India because of lack of proper knowledge in breeding behaviour, the non-availability of the quality seed and grow-out technology. In this current study, semi-artificial (induce) breeding of A. testudineus was conducted for the mass seed production of this species in an earthen pond.